Oral Anticoagulant Treatment in Patients with Atrial Fibrillation and Chronic Kidney Disease - Mihai Ciprian Stoica; Zsolt Gáll; Mirela Liana Gliga; Carmen Denise Căldăraru; Orsolya Székely (Medicina, 2021)
Over the past few decades, a series of innovative medicines have been developed in order to optimize anticoagulation therapy for atrial fibrillation (AF). As a result, a number of nonvitamin K antagonist oral anticoagulants (NOAC) that directly target the enzymatic activity of factor II and factor Xa have been successfully licensed providing a more predictable effect and better safety profile compared to conventional anticoagulants (heparins and vitamin K antagonists (VKAs)). However, comparative efficacy and safety data is limited in patients with advanced chronic kidney disease (i.e., CKD stage 4/5 and end stage renal disease) because patients with estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m2 were actively excluded from landmark trials, thus representing a major clinical limitation for the currently available agents. However, the renal function of AF patients can be altered over time. On the other hand, patients with CKD have an increased risk of developing AF. This review article will provide an overview of current concepts and recent evidence guiding the clinical use of NOACs in patients with CKD requiring chronic anticoagulation, and the associated risks and benefits of treatment in this specific patient population.